2014
DOI: 10.1128/mbio.01683-14
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Analysis of the Global Regulatory Networks Active in Pseudomonas syringae during Leaf Colonization

Abstract: The plant pathogen Pseudomonas syringae pv. syringae B728a grows and survives on leaf surfaces and in the leaf apoplast of its host, bean (Phaseolus vulgaris). To understand the contribution of distinct regulators to B728a fitness and pathogenicity, we performed a transcriptome analysis of strain B728a and nine regulatory mutants recovered from the surfaces and interior of leaves and exposed to environmental stresses in culture. The quorum-sensing regulators AhlR and AefR influenced few genes in planta or in v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

10
90
2

Year Published

2015
2015
2018
2018

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(104 citation statements)
references
References 83 publications
10
90
2
Order By: Relevance
“…This study also found that AlgU-dependent transcription was induced in response to osmotic stress (21), and there is a great deal of overlapping regulation between the osmotic stress stimulon and the algU regulon in P. syringae pv. syringae B728a, suggesting that osmolarity is a key signal for AlgU activation in this pathovar (21,22). But, the role of AlgU may be different in P. syringae pv.…”
supporting
confidence: 54%
See 3 more Smart Citations
“…This study also found that AlgU-dependent transcription was induced in response to osmotic stress (21), and there is a great deal of overlapping regulation between the osmotic stress stimulon and the algU regulon in P. syringae pv. syringae B728a, suggesting that osmolarity is a key signal for AlgU activation in this pathovar (21,22). But, the role of AlgU may be different in P. syringae pv.…”
supporting
confidence: 54%
“…syringae B728a growing in plants and under a variety of in vitro conditions indicated that AlgU regulates genes for alginate biosynthesis as well as for type VI secretion and oxidative and osmotic stress responses (21). This study also found that AlgU-dependent transcription was induced in response to osmotic stress (21), and there is a great deal of overlapping regulation between the osmotic stress stimulon and the algU regulon in P. syringae pv. syringae B728a, suggesting that osmolarity is a key signal for AlgU activation in this pathovar (21,22).…”
mentioning
confidence: 60%
See 2 more Smart Citations
“…There is precedence for such a restricted QS regulon. Only a small subset of genes is activated in the photosynthetic bacterium Rhodopseudomonas palustris (33), as well as in the plant pathogen Pseudomonas syringae (34). This is in stark contrast to the QS systems of Pseudomonas aeruginosa, which regulate hundreds of genes (35,36).…”
Section: Discussionmentioning
confidence: 95%